2015
DOI: 10.2466/49.cp.4.11
|View full text |Cite
|
Sign up to set email alerts
|

Prosocial Propensity Bias in Experimental Research on Helping Behavior: The Proposition of a Discomforting Hypothesis

Abstract: When researchers fail to control for confounding factors, the causes of behavior can be more apparent than real, even in experimental research. The current study replicates an experiment by Weinstein, Przybylski, and Ryan (2009) with the goal of demonstrating that their main fi nding could have resulted from diff erences in people's prosocial propensity. In their research, they found their hypothesized interaction eff ect: depending on the extent of immersion, participants presented with images of nature were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…In turn, ecological behavior is defined as behavior that directly (e.g., saving energy at home) or indirectly (e.g., supporting campaigns that promote the use of renewable energy) affects humanity's impact on the natural environment, and behavior that aims to raise awareness of environmental problems (e.g., pointing out environmental damage to others) [5]. Many researchers have suggested that ecological behavior can be conceptualized as a type of prosocial behavior [6,7], driven by the same general propensity as prosocial behavior benefitting human others. This propensity is referred to as "prosocial propensity" and is defined as an individual's willingness to act prosocially regardless of the domain in which this behavior may be enacted [8].…”
Section: Rationale Human and Ecological Domains Of Prosocial Behaviormentioning
confidence: 99%
“…In turn, ecological behavior is defined as behavior that directly (e.g., saving energy at home) or indirectly (e.g., supporting campaigns that promote the use of renewable energy) affects humanity's impact on the natural environment, and behavior that aims to raise awareness of environmental problems (e.g., pointing out environmental damage to others) [5]. Many researchers have suggested that ecological behavior can be conceptualized as a type of prosocial behavior [6,7], driven by the same general propensity as prosocial behavior benefitting human others. This propensity is referred to as "prosocial propensity" and is defined as an individual's willingness to act prosocially regardless of the domain in which this behavior may be enacted [8].…”
Section: Rationale Human and Ecological Domains Of Prosocial Behaviormentioning
confidence: 99%
“…For example, although self-reported immersion (Ryan et al, 2010;Weinstein et al, 2009) and individual differences in the perceived beauty of nature (Zhang et al, 2014) have been shown to moderate effects of exposure to natural images, past theory does not specify the origins of individual differences in immersion and perceived beauty and their specific psychological underpinnings. Indeed, others have critiqued the use of measured individual difference variables, and the ability to draw causal conclusions based on these, in this kind of research (Kaiser, Otto & Schuler, 2015). Current frameworks also do not seem well-placed to explain restorative effects that follow exposure to distinctly urban environments (e.g., Studies 1 & 2).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…At least in the domain of environmental attitude, we were able to identify an alternative measure that was based on the Campbell paradigm, that is, the GEB. Beyond the promising results of our rather basic comparison study on construct validity, other studies using the GEB have already provided results on its good external validity with respect to actual behavior [ 22 , 35 , 36 ]. Even though the GEB is not based on independently observed behavioral responses and is instead based on self-reported behavior, its outcome corresponds well with actual behavior and even the ecological impact of the behavior [ 37 ].…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, because the Campbell paradigm is based on the Rasch model, all the benefits that come with the Rasch model, such as adaptive testing, can be used and applied (e.g., [ 38 ]). For instance, the possibility to link two test of the same construct with only a few items that overlap, repeated measurement becomes much more convenient (e.g., [ 35 ]).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation